Anesthetic effectiveness of tekelan leaves on tinfoil barb fish in closed transportation - Eva Ayuzar; Rachmawati Rusydi; Hayatun Muna; Muliani Muliani (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The mortality of tinfoil barb during transportation is relatively high due to the oxygen consumption rate and excretion of these fishes. Therefore, the use of an appropriate anesthetic drug becomes one of the solutions for solving this transportation problem of tinfoil barb. One of the natural anesthetic drugs with potential to be studied is Chromolaena odorata leaves. The purpose of this study is to evaluate the effectiveness of anesthetic compounds from Chromolaena odorata leaves in the closed transportation of tinfoil barb. The experimental design used was a non-factorial completely randomized design that consisted of four treatments and three replications,then followed by a Tukey test to see if there was a significant difference. The experimental treatments were A (0 ml/L of leaves filtrate), B (80 ml/L of leaves filtrate), C (90 ml/L of leaves filtrate), and D (100 ml/L of leaves filtrate). The observed parameters were fish behavior towards unconscious condition, onset time, immotilization time, survival rate, and water quality. The results showed that the shortest onset time was obtained from treatment D (100 ml/L leaves filtrate), namely 58 minutes towards unconscious condition, then the longest immotilization time was also shown by treatment D, which was 371 minutes. The highest survival rates were also shown by treatment D which were 94,33% during transportation and 76,33% during culture. The water quality parameters during the experiment were in an optimum condition of tinfoil barb.Keywords:AnestheticChromolaenaodorataTransportationTinfoil barb